DNA Sequences of Ca2+-ATPase Gene in Rice KDML 105 - Sakonwan Prasitwilai; Sripan Pradermwong; Amara Thongpan; Mingkwan Mingmuang (Agriculture and Natural Resources, 2006)
Total RNA isolated from the leaves of KDML 105 rice was used as template to make complementary DNA (cDNA). Primer combinations of CA1-CA10 which were designed from Lycopersicon esculentum and Arabidopsis thaliana Ca2+-ATPase gene sequence were used. The nucleotide sequences amplified from 7 primer combinations gave 2,480 bp (fragment A). This fragment was found to be 99% homology to that of the putative calcium ATPase of Oryza sativa (Japonica cultivar-group) as shown in the GenBank. Amplification of 3′ end fragment done by Rapid Amplification of cDNA Ends (3′RACE) technique using 3′GSP1, 3′GSP2, and 3′UAP as primers gave a DNA fragment of 933 bp having an overlapping region with DNA fragment A, which resulted in the combined length of 2,944 bp (fragment B). To find the sequence of 5′ end, 5′RACE technique was used having 5′GSP1, 5′GSP2, 5′ AP and 5′UAP as primers. It gave a DNA fragment of 473 bp showing an overlapping region with DNA fragment B, which ultimately resulted in the combined length of 3,331 bp (total CA). The deduced 1,008 amino acid sequence of total CA showed 99% homology to putative calcium ATPase of O. sativa (Japonica cultivar-group) cv. Nipponbare. The higher percent homology of this Ca2+-ATPase gene in KDML105 to that of O. sativa cv. Nipponbare (99%) than to O. sativa cv. IR36 (89%) was not as anticipated since both KDML105 and O. sativa cv. IR36 belong to the same Indica type while O. sativa cv. Nipponbare is a Japonica. Analysis of the amino acid sequences of Ca2+- ATPase gene indicated that this gene in KDML105 most likely belonged to ER type IIA group.